RECORD OF AN UNUSUALLY LARGE SPECIMEN OF LACTARIUS LACTARIUS (SCHNEIDER) - Kunjipalu, K K (Indian Journal of Fisheries, 2011)
A specimen of Lactarius lactarius (Schneider) measuring 350 mm in totallength, the largest to be recorded so far, was caught off Veraval, northwest coastof India. The previous known record was that of a specimen measuring 330 mmin total length from Gulf of Mannar, southeast coast of India (Shanmughavelu1973),